Biodegradation of the Antituberculosis Drug Isoniazid in the Aquatic Environment. Issue 2 (2nd June 2014) - Sasu, Samuel; Metzger, Jörg; Kranert, Martin; Kümmerer, Klaus
<x xml:space="preserve">Abstract</x> As part of our study on pharmaceutical waste management in Ghana, we investigated the biodegradability of the most widely used antituberculosis drug isoniazid in the aquatic environment. The experiment was conducted using three tests from the Organization for Economic Co‐operation and Development guidelines (close bottle test (CBT) 301D, low bacterial density i.e. <1000 colony forming units (CFU) mL−1, manometric respiratory test (MRT) 301 F, i.e. <1000 CFU mL−1 and the Zahn‐Wellens test (ZWT) 302B, i.e. <1000 CFU mL−1) employing different concentrations. At the end of the study, the results showed that isoniazid at concentrations of 4.29 mg L−1 for the CBT and 25.7 mg L−1 for the MRT were found not to be readily biodegradable in accordance with the test guidelines. In the ZWT, at a concentration of 142.92 mg L−1 which allows evaluation of aerobic degradation at high bacterial density, the results provided evidence for biological degradation of isoniazid. Finally, the test samples after 28 days analyzed by high performance liquid chromatography coupled to ultraviolet detector showed a complete primary elimination of the test substance in MRT and ZWT. The difference of the results obtained by HPLC and oxygen consumption in the MRT indicated the formation of stable transformation products, i.e. incomplete biodegradation, whilst there was no biodegradation at all in CBT.